Post-transcriptional regulation of TbIF1 in life cycle of Trypanosoma brucei - Gratzl, Sascha (Jihočeská univerzita, 2020)
TbIF1, a protein Inhibitor of F1-ATPase in Trypanosoma brucei, is expressed exclusively in the insect stage of the parasite. In the bloodstream form, TbIF1 is switched off, because its activity interferes with the essential role of the ATP synthase in the maintenance of the mitochondrial membrane potential. Here, we employ a series of reporter genes to study the impact of 3'UTR of TbIF1 on mRNA stability and translatability to get insight into the tight post-transcriptional control of TbIF1. We provide evidence that developmentally regulated RNA binding protein Rbp10 is critical for downregulation of TbIF1 on translation level in bloodstream-form trypanosomes.
Post-transcriptional regulation of TbIF1 in life cycle of Trypanosoma brucei
Keywords: Trypanosoma brucei; post-transcriptional regulation; ATP synthase; RT-qPCR; ribosmome profiling; ELISA; Chloramphenicol acetyltransferase; reporter system; RNA binding protein; Rbp10; Rbp6; translation efficiency; Trypanosoma brucei; post-transcriptional regulation; ATP synthase; RT-qPCR; ribosmome profiling; ELISA; Chloramphenicol acetyltransferase; reporter system; RNA binding protein; Rbp10; Rbp6; translation efficiency